Timeline of the World Polonia Winter Games (1986-2016) - Leonard Nowak; Maria Alicja Nowak (Jan Długosz University in Częstochowa, 2019)
Keeping the chronological order, this paper presents a timeline of events of the 30-year history of the organization of the Polonia Winter Games in Poland: first their beginnings in the years 1986-1989, and then, after a long break and a change to the name, their continuation as the World Polonia Winter Games in the years 2000-2016. Driven by the popularity of the summer Polonia Sports Games (1934-1991), and later the World Polonia Games in Poland (1997-2015), Polish diaspora organizations from different parts of the world decided to organize the 1st Polonia Winter Games in Zakopane in 1986. In accordance with the guidelines, also accepted by the International Commission for the Games, the first three of them (1986, 1989, 1992) took place every three years. After an eight-year break, winter sports meetings of Polonia people were reactivated in the year 2000, when the next 4th Polonia Winter Games were held in the Beskidy Mountains. That year, they were named the World Polonia Winter Games, a name which has remained until this day. It was agreed that they should be organized every two years. The aim of this work is to present the second part of the timeline of events, which are related to the organization and the course of the World Polonia Winter Games (1986-2016). The concept adopted by the authors stems not only from the extensive chronology, but also from the vastness of source material. Many athletes representing various Polish diaspora communities participated in the Polonia Winter Games, and later in the World Polonia Winter Games. The program of the Games underwent gradual changes. From the beginning of the Winter Games there were no sporting performance minimums. Age categories were extended in order to enable young, middle-aged and older people to compete in the Games, thus making it possible for them to take part both in sports contests and recreational events. The Polonia Games gave impetus to association of Polish athletes in Polonia sports organizations abroad and contributed largely to the consolidation of Polish national life in exile.They provided an opportunity to improve the knowledge of the Polish language, learn about the country of the ancestors and its achievements in various fields of social, cultural, and sporting life. Polonia activists together with sports activists in Poland decided to continue the World Polonia Winter Games for the sake of the whole Polish diaspora and Poles living in Poland.